Monitoring tooth demineralization using a cross polarization optical coherence tomographic system with an integrated MEMS scanner - Fried, Daniel (2012)
New methods are needed for the nondestructive measurement of tooth demineralization and remineralization to monitor the progression of incipient caries lesions (tooth decay) for effective nonsurgical intervention and to evaluate the performance of anti-caries treatments such as chemical treatments or laser irradiation. Studies have shown that optical coherence tomography (OCT) has great potential to fulfill this role since it can be used to measure the depth and severity of early lesions with an axial resolution exceeding 10-µm, it is easy to apply in vivo and it can be used to image the convoluted topography of tooth occlusal surfaces. In this paper we present early results using a new cross-polarization OCT system introduced by Santec. This system utilizes a swept laser source and a MEMS scanner for rapid acquisition of cross polarization images. Preliminary studies show that this system is useful for measurement of the severity of demineralization on tooth surfaces and for showing the spread of occlusal lesions under the dentinal-enamel junction.